PENGARUH NPL, LDR, BOPO TERHADAP ROA PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2021 - Pitaloka Andry Kirana; Dwi Eko Waluyo (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
This research aims to determine the effect of NPL, LDR, and BOPO to the ROA of conventional commercial banks listed on the Indonesia Stock Exchange 2012-2021. Population in this research while sample was defined by using purposive sampling method and 8 Banks as sample, so that if you add up there are 80 samples (n). Type of data that we used was secondary data (panel data) from www.ojk.go.id. The analysis method has been done by using multiple linear regressions analysis. Hypothesis testing uses t statistical test, F statistic test and coefficient of determination. The results shows that NPL and BOPO variables have a significant negative effect on ROA and the LDR variable has a significant positive effect on ROA.